Risk perception and priority setting for intervention among hepatitis C virus and environmental risks: a cross-sectional survey in the Cairo community - Dewedar Sahar; Gad Rita R; Mohamed Mostafa K; Schwarzinger Michaël; Fontanet Arnaud; Carrat Fabrice; Luchini Stéphane (BMC Public Health, 2010)
Abstract Background Hepatitis C virus (HCV) recently emerged as a major public health hazard in Egypt. However, dramatic healthcare budget constraints limit access to the costly treatment. We assessed risk perception and priority setting for intervention among HCV, unsafe water, and outdoor air pollution in Cairo city. Methods A survey was conducted in the homes of a representative sample of household heads in Cairo city. Risk perception was assessed using the "psychometric paradigm" where health hazards are evaluated according to several attributes and then summarized by principal component analysis. Priority setting was assessed by individual ranking of interventions reducing health hazards by 50% over five years. The Condorcet method was used to aggregate individual rankings of the three interventions (main study) or two of three interventions (validation study). Explanatory factors of priority setting were explored in multivariate generalized logistic models. Results HCV was perceived as having the most severe consequences in terms of illness and out-of-pocket costs, while outdoor air pollution was perceived as the most uncontrollable risk. In the main study (n = 2,603), improved water supply received higher priority than both improved outdoor air quality (60.1%, P < .0001) and screening and treatment of chronic hepatitis C (66.3%, P < .0001), as confirmed in the validation study (n = 1,019). Higher education, report of HCV-related diseases in the household, and perception of HCV as the most severe risk were significantly associated to setting HCV treatment as the first priority. Conclusions The Cairo community prefers to further improving water supply as compared to improved outdoor air quality and screening and treatment of chronic hepatitis C.